Yelim Philanthropy: Exploring Social Cohesion and Alignment with Sharia Economic Law in Kei Society - Awaluddin, Syah; Uar, Eka Dahlan; Soeleman Djaiz Baranyanan; Nurhayati; Bin Ali, Mohamad Fairuz (Sekolah Tinggi Agama islam Negeri Majene, 2025)
The practice of Yelim as a form of interfaith philanthropy has yet to be scrutinised in the intersecting fields of legal sociology and Islamic economic law. The purpose of this study is to reveal the practice of Yelim in encouraging legal consciousness and social cohesion in the Kei Community and to show the harmony of its practice under the principles of Sharia economic law. This study is qualitative research under the phenomenological approach to deeply interpret the practice of Yelim with a focus on philanthropy, and fund management. Data were obtained through interviews, observation and documentation. The results disclose that Yelim is undertaken accountably by traditional figures and community members. The funds have been used for social purposes, including weddings, funerals, religious buildings, and education support. The philanthropy of both Muslims and Christians in the collection and utilisation exemplifies social solidarity and the principle of distributive justice. According to Islamic economic law, the philanthropy management has been in line with maqāṣid al-sharī'a in the principles of Hifzh al-Nafs and Hifzh al-Māl, linking to maslahah, trust, humanity and justice. The tradition undertaken has shown the legal awareness rooted in social norms and ancestral values, not merely formal legal texts. Yelim serves as a model for integrating customary law and Sharia economic principles in multicultural communities.